Effects of formal home care on spousal health outcomes - Gonçalves, Judite (2021)
This study estimates the impacts of formal home care provided by paid professionals on spousal health outcomes. We use data from the Survey of Health, Ageing, and Retirement in Europe, a panel of older adults living in several European countries, and match new formal home care users to non-users to account for the endogeneity of the decision to seek formal home care. After considering underlying mechanisms, our results suggest that at least in the short run, the use of formal home care does not impact spousal physical or mental health. We also find that formal home care use increases spousal informal caregiving —along the extensive margin—, although in our sample and short time horizon, spousal informal caregiving does not seem to impact health.